Diversity, Status and Abundance of Avian fauna in and around Jalna Urban, M.S., India - Harde, Satish N.; Shinde, Laxmikant V.; Phalke, Ganesh B. (International Journal of Scientific Research in Biological Sciences, 2020)
The present study conducted to investigate the diversity, distribution, status and abundance of Avian fauna in and around Jalna urban. We surveyed Wetland (Lakes, Ponds), Kundlika river, Forest, Grassland and Agriculture areas from June 2018 to December 2019. The result of present study reveals total 97 species of birds belonged to 48 families. Highest number 68 of bird species observed from agricultural areas, 57 species from forest areas, 41 species from Kundalika River and 32 species from wetlands. According to Status of birds 72 (74.22%) birds’ species were residential, 9 (9.27%) were winter migrant, some 12 (12.37%) local migrant and 4 (4.12%) found passage migrants. Considering abundance, 43 (44.32%) birds’ species were commonly seen, 18 (18.55%) species were very common, 27 (27.83%) species were not rare but not common whereas 9 (9.27%) species were rare. Winter migrant species were Greater flamingoes, Eurassian spoonbills, Painted stork, Bar headed goose, Barn swallow, Common sandpiper, Ruddy shelduck. Rare species of bird in Jalna were Common hoopoe, spotted owlet, Wooly necked stork and Yellow fronted woodpecker, Indian Grey hornbill. For conservation point of view there is need of time to protect forest areas and wetlands through proper administration and legislation. Beside plantation of bird attracting plants and development of new habitat may lead to increase in the species richness in the district.